2020
DOI: 10.1080/03639045.2020.1717516
|View full text |Cite
|
Sign up to set email alerts
|

Design and optimization of a child-friendly dispersible tablet containing isoniazid, pyrazinamide, and rifampicin for treating tuberculosis in pediatrics

Abstract: Objective: Develop a child-friendly Fixed Dose Combination (FDC) water-dispersible tablet for Tuberculosis (TB) treatment, with 50, 150 and 75 mg of isoniazid (INH), pyrazinamide (PZA) and rifampicin (RFP) respectively. This new formulation must contain the lowest possible number of excipients, all accepted for pediatrics, and fulfill all the pharmacopoeia requirements for this type of tablet (friability, disintegration time, fineness of dispersion and content uniformity).Significance: TB is an infectious dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…All samples and solvents were filtered with 0.2 µm pore-size filters (Millipore, Billerica, MA, USA) and degassed. The method has been validated in a previous work [19] and is a simple stability-indicating method, which allowed us to detect and quantify the first-line drugs used in TB treatment as pure patterns and after its extraction from formulations, accurately and precisely. Figure 1 shows the control charts for the methods where the areas of the peaks stay between the established limits every time.…”
Section: Ultra Performance Liquid Chromatography (Uplc) Methodsmentioning
confidence: 99%
“…All samples and solvents were filtered with 0.2 µm pore-size filters (Millipore, Billerica, MA, USA) and degassed. The method has been validated in a previous work [19] and is a simple stability-indicating method, which allowed us to detect and quantify the first-line drugs used in TB treatment as pure patterns and after its extraction from formulations, accurately and precisely. Figure 1 shows the control charts for the methods where the areas of the peaks stay between the established limits every time.…”
Section: Ultra Performance Liquid Chromatography (Uplc) Methodsmentioning
confidence: 99%
“…Tuberculosis (TB) remains a major global health problem present in every country in the world, regardless of the availability of standard treatment guidelines [1,2]. It is the leading cause of death from a single infectious agent, ranking above the Human Immunodeficiency Virus (HIV) with about 10 million new active infections and 1.5-2 million fatalities annually [1,[3][4][5]. TB is an airborne, highly contagious disease often spread by coughing and sneezing.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceutics 2020, 12, 286 2 of 15 childhood deaths each year [1,3,6]. The TB mortality rate is 70% higher in children under the age of five than it is in adults in high burden areas [1,8].…”
Section: Introductionmentioning
confidence: 99%
“…To date, commonly used pharmaceutical formulations are either liquid dosage forms (e.g., solutions, suspensions), fixed dose dispersible tablets and in most instances, adult tablets are often broken, crushed or mixed with food or water (co-administration) to make pediatric management possible [12][13][14][15]. Despite the availability of a few commercialized pediatric preparations, considerable global scarcity still exists, meaning that many children are unable to access these medicines [15][16][17][18][19]. Moreover, studies have shown that co-administration (with food, water etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Dispersible tablets on the other end are deemed more child-friendly but still limited in that they are difficult to administer while in transit or when there is reduced/no access to potable water-like in most underdeveloped and developing countries where TB is endemic. They usually contain additives that are either not safe for use in children or hygroscopic in nature, making them prone to atmospheric moisture/water absorption that can lead to active drug instability, eventual inactivity and possible pharmacotherapeutic inefficacy [17,19,23]. Other potentially applicable delivery systems for children include chewable tablets, which are often more suitable for older children (>3 years) with teeth, and sprinkles, though they are more acceptable for older children that can eat solid food [23,24].…”
Section: Introductionmentioning
confidence: 99%